Friends-Based Protective Strategies and Unwanted Sexual Experiences: A Daily Diary Examination of First Year College Women. (June 2022) - Blayney, Jessica A.; Jenzer, Tiffany; Jaffe, Anna E.; Carroll, Quinn; Read, Jennifer P.
Risk for unwanted sexual experiences can emerge in social contexts—the same contexts that early college women navigate with their friends. Though friends naturally engage in prevention strategies, less is known about how capable guardianship influences risk. Using multilevel structural equation modeling, the present study examined guardianship at the person- and situation-level. First year college women ( N = 132) completed eight weekends of daily surveys. We examined whether guardianship (e.g., more friends present, greater proportion of female friends, no intoxicated friends) would reduce unwanted sexual experience risk and if this relation was mediated by friends-based strategy use. An alternative model was also tested with the same predictors, but unwanted sexual experiences as the mediator and friends-based strategy use as the outcome. Over half (58%) of extended weekend nights with friends involved drinking or using drugs. Friends-based strategies were used on 29% of nights. Across models, being with one or more intoxicated friends was associated with friends-based strategy use and an unwanted sexual experience, but only at the situation-level. Parents, educators, and policy makers can encourage college women to draw on their social networks to enhance safety. Interventions could incorporate more universal strategies for responding to risk in social contexts.